Opera out of the box 2009-2019 : the Cahn years at Opera Vlaanderen - Battistelli, Giorgio 1953- (Stockmans Art Books, 2019)
The breakthrough years of Aviel Cahn at Opera Vlaanderen have been collected in a book. As it turns out this is not your regular publication. Gesamtkunstwerk is a description often used, sometimes even leaning towards the cliché, but in the case of 'Opera Out of the Box' it fits well.0In 2008, Aviel Cahn is appointed as the youngest opera intendant in Europe at 33 years old. Concerns about his age are countered by the highest expectations about Cahn being a visionary personality and a magnet to address and attract highly talented artists and performers on an international level. This monumental book is housed in an arty slipcase with three different covers, with pictures by the artists that collaborated with Cahn on communicating and working around the seasonal themes during the last five years; as such contemporary artists Koen van den Broek, Kati Heck and Maurizio Cattelan (ToiletPaper) found a new gallery space in their collaboration with Opera Vlaanderen. 'Opera Out of the Box' takes the reader on a trip of seventy productions from the last decade. Moving from text to image, the book then turns into a 200 page photo gallery, a true feast for the eye.
"The texts were written in either English, German, Italian or Dutch and translated in the other language." -- Colophon
Keywords: Cahn, Aviel -- 1974-; Opera Ballet Vlaanderen; Geschichte 2009-2019; Opernproduktion; Bildband; Festschrift